(untitled) (Iraqi Journal of Science, 2023)
The dramatic decrease in the cost of genome sequencing over the last two decades has led to an abundance of genomic data. This data has been used in research related to the discovery of genetic diseases and the production of medicines. At the same time, the huge space for storing the genome (2–3 GB) has led to it being considered one of the most important sources of big data, which has prompted research centers concerned with genetic research to take advantage of the cloud and its services in storing and managing this data. The cloud is a shared storage environment, which makes data stored in it vulnerable to unwanted tampering or disclosure. This leads to serious concerns about securing such data from tampering and unauthorized searches by those involved. In addition to securing inquiries, making calculations on this data, and generating differential privacy and garbled circuits, cryptography is considered one of the important solutions to this problem. This paper introduces most of the important challenges related to maintaining privacy and security and classifies each problem with appropriate, proposed, or applied solutions that will fuel researchers’ future interest in developing more effective privacy-preserving methods for genomic data.